Arabic idiomatic phrases learning courseware for non-native speakers - Sahrir, Muhammad Sabri; Nawi, Amani (2014)
Idiomatic phrases are words that have hidden meaning different than the literal meaning of the words. In this sense, Arabic language is similar to English language as it has thousands of idioms that are used quite extensively in conversations, movies and especially in writings as a better way to express the thought and emotion that does not fit into words. The problem is Arabic idioms are rarely becoming a center of focus in class lessons, whereas there are only few books available for the learners as a guide to idioms and its usage, and the same goes to learning courseware. The objective of this study is to design and develop a prototype of computer-assisted courseware for Non-native Arabic learners in learning Arabic Idioms based on the difficulties encountered by the using a survey of “Learners’ Need Questionnaire”. Feedbacks of learning strategy, learner’s early perception, suggestion and comment towards the design and the development of the prototype courseware are also collected through the same questionnaire. The sampling population of this study consists of randomly selected 70 students from Department of Arabic Language and Literature at International Islamic University Malaysia (IIUM), lecturers and experts in subject-matter (SME) and instructional design (ID). The method used in this study is a descriptive and analytical method. The design and the development of the prototype courseware are based on Behavioral Theory by Skinner and Cognitive Theory of Multimedia Learning by Mayer, while the ADDIE Model is chosen as a generic ID model in designing and developing the prototype courseware. Findings from this study indicated that students who faced the difficulties in learning Arabic Idioms are due to few factors such as; Arabic Idioms were not specifically being taught in class as well as there is no separate subject focusing in teaching Arabic Idioms. In addition, learners appear to read less Arabic books which does not help them in identifying Arabic Idioms encountered in text and the most noticeable reason is Arabic Idioms is highly related to the Arab’s culture and the way they convey the ideas are unique to a particular region or country or society. Plus, the analysis from qualitative data showed that learner’s preference for using this courseware in learning Arabic Idiomatic phrases based on their comments on the usability, learning contents and effectiveness. Suggestions and comments are collected from learner’s open-ended survey and incorporated with the findings of this study as a future guide to enhance this prototype of computer-assisted courseware for learning Arabic Idiomatic phrases.